Hubungan Sikap Kerja Berdiri Dan Hubungan sikap kerja berdiri dan shift kerja dengan perasaan kelelahan pada petugas operator SPBU - Subhan ZulArdi (Jurnal Kesmas Prima Indonesia, 2022)
ABSTRACT Fatigue is a subjective feeling experienced by a person after doing his activities such as tiredness, drowsiness, boredom, and thirst. The problem found at The Margonda Raya Road gas station with 5 workers there are complaints of work fatigue that is felt heavier during the morning shift work, because the activities of gas station operators pretty much serve consumers and the attitude of work done by standing static. This study was conducted to find out the relationship between standing attitude and work shift with feeling fatigue in the operator officer of gas station Margonda Raya road number 328 Depok City, West Java. This research uses a type of analytical observational quantitative research with cross sectional design. The research located at gas station Margonda Raya road number 328 Depok City, West Java with a sample of 34 people and sampling techniques is total sampling. Data analysis using chi square test. The instruments used were Fatigue Assessment Scale (FAS) questionnaires, Rapid Entire Body Assessment (REBA) worksheets and cameras. Based on the results of the study there is a correlation between work shifts and work fatigue (p-value = 0.036) but there is no correlation between standing work attitudes and feelings of fatigue (p-value = 0.704 and RP = 1,571). The Conclusion There is a significant correlation between work shifts and feelings of fatigue but there is no significant correlation between standing attitude and feelings of fatigue at the operator of gas station Margonda Raya road number 328 Depok City, West Java.